Numerical modelling for nanoparticle thermal migration with effects of shape of particles and magnetic field inside a porous enclosure - Babazadeh, Houman; Zeeshan, A.; Jacob, Kavikumar; Hajizadeh, Ahmad; Bhatti, M. M. (Springer, 2020)
Computational modelling for nanoparticle migration inside a permeable space has been reported. Impacts of shape factor and radiation were included in the mathematical model. CVFEM was employed to analyse magnetic force impact. Impacts of magnetic radiative parameters, buoyancy forces and nanoparticle shape on nanomaterial behaviour were demonstrated. Utilizing the Darcy model helps us to predict the behaviour of porous media. Outputs revealed higher convective mode can be achieved with augmenting buoyancy force while opposite outcome appears when magnetic field is imposed. Thermal plume vanishes with the rise of conductive mode which is gained as Hartmann increases.